1997
DOI: 10.1063/1.118237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of α-HgI2 epitaxial growth on the defect structure of CdTe:Ge substrates

Abstract: The ␣-HgI 2 /CdTe:Ge heterostructures have been studied by cathodoluminescence ͑CL͒ in the scanning electron microscope. The ␣-HgI 2 expitaxial growth was shown to cause an enhancement of the CL intensity in a layer of the substrate extending up to about 500 m from the ␣-HgI 2 /CdTe:Ge interface. CL spectra of the layer reveal the appearance of a band related to tellurium vacancies as well as the decrease of the emission attributed to defect complexes involving Ge. The data obtained indicate that Ge-impurity g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…2a, the PL spectrum recorded in the substrate middle (area 1 of Fig. 1b) exhibits the PL bands which are generally present in as-grown CdTe:Ge crystals and have been studied by us previously [18,20,21]. The typical PL spectrum at 80 K contains the near-band-gap FE and D-h emission, positioned at 1.580 eV (Ref.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…2a, the PL spectrum recorded in the substrate middle (area 1 of Fig. 1b) exhibits the PL bands which are generally present in as-grown CdTe:Ge crystals and have been studied by us previously [18,20,21]. The typical PL spectrum at 80 K contains the near-band-gap FE and D-h emission, positioned at 1.580 eV (Ref.…”
mentioning
confidence: 98%
“…It was suggested that two phenomena, which could lead to the observed improvement of CdTe properties relevant to the fabrication of radiation detectors, are the dissolution of Te precipitates and an elimination of non-radiative channels of recombination due to the residual impurity outdiffusion during the VPE process [17][18][19]. Following that research, in this paper we present the results on the photoluminescence (PL) study of CdTe:Ge substrates, which form part of Hg 1Àx Cd x I 2 /CdTe heterostructures grown by the low-temperature (o250 C) VPE, using a combination of several PL techniques such as spectroscopy, cross-section mapping and profiling.…”
mentioning
confidence: 99%
“…13 The capability to obtain both spectral and spatial resolution allows us to gain quite valuable information about the defect structure of the material. Though bulk crystals have been extensively studied by luminescence techniques, not so much work has been done to characterize CdTe epitaxial layers.…”
Section: ͓S0003-6951͑97͒01947-5͔mentioning
confidence: 99%
“…Recently, an example of the technological compatibility of HgI 2 and CdTe has been demonstrated by growing HgI 2 and Hg 1Ϫx Cd x I 2 layers on CdTe substrates by vapor phase epitaxy ͑VPE͒. 8,9 Despite significantly different crystallographic structures of the layer and the substrate ͑layered tetragonal 10 and cubic zinc blende 11 types, respectively͒, Hg 1Ϫx Cd x I 2 /CdTe heterostructures have shown a good stability at room and elevated temperature and a structural and compositional uniformity of the layer in the wide composition range of xϽ0.7.…”
Section: Introductionmentioning
confidence: 99%
“…The structural defects in CdTe substrates generated by the VPE growth has recently been studied by the cathodoluminescence microscopic technique. 9 Following this work, in the present article we report on the structural defects in Hg 1Ϫx Cd x I 2 VPE layers studied by scanning electron microscopy ͑SEM͒ and high resolution synchrotron x-ray topography ͑SXRT͒.…”
mentioning
confidence: 99%